IMPROVING THE HYDRAULIC CALCULATION METHOD FOR BOTTOM EDDIES IN THE CONFLUENCE OF FLOW IN DEFORMABLE CHANNELS (Innovative technologies, 2026)
Under the influence of the vortex zone formed at the confluence of two channels, sediments intensively settle. Taking these sediments into account, the hydraulic and geometric parameters of the flow are determined. The analytical solution shows that at the confluence of flows, where the secondary channel (Channel 2) joins the main channel (Channel 3), the streamlines bend and contract. This leads to the emergence of a transverse flow. As the flow impacts the left bank of the main channel (Channel 3) and moves toward the right bank, a vortex flow is generated. The resulting vortex flow causes sediment accumulation on the right bank at the inlet section, while the remaining sediments are transported at high velocity in the contraction zone. The high velocity in the contraction section may lead to erosion of the left bank of the main channel (Channel 3). The solution to this issue is explored by varying the angle of channel confluence. During the solution process, the velocity distribution in the channels, as well as the shape and dimensions of the vortex zone, are determined analytically.
Keywords: flow confluence; cavitation; vortex zone; velocity; flow velocity; reflection; complex potential; confluence angle